A Comparative Study of Some Central Notions of ASPIC+ and DeLP. Issue 3 (10th May 2020) - GARCÍA, ALEJANDRO J.; PRAKKEN, HENRY; SIMARI, GUILLERMO R.
Abstract: This paper formally compares some central notions from two well-known formalisms for rule-based argumentation, DeLP and ASPIC + . The comparisons especially focus on intuitive adequacy and inter-translatability, consistency, and closure properties. As for differences in the definitions of arguments and attack, it turns out that DeLP 's definitions are intuitively appealing but that they may not fully comply with Caminada and Amgoud's rationality postulates of strict closure and indirect consistency. For some special cases, the DeLP definitions are shown to fare better than ASPIC + . Next, it is argued that there are reasons to consider a variant of DeLP with grounded semantics, since in some examples its current notion of warrant arguably has counterintuitive consequences and may lead to sets of warranted arguments that are not admissible. Finally, under some minimality and consistency assumptions on ASPIC + arguments, a one-to-many correspondence between ASPIC + arguments and DeLP arguments is identified in such a way that if the DeLP warranting procedure is changed to grounded semantics, then 's DeLP notion of warrant and ASPIC + 's notion of justification are equivalent. This result is proven for three alternative definitions of attack.